(untitled) (Canadian Rheumatology Today, 2024)
Osteoporosis is a chronic condition characterized by decreased bone mineral density (BMD) and deterioration of bone architecture, leading to an increased risk of fractures. It is the most common metabolic bone disease globally. It is estimated that more than two million Canadians aged 40 years and older have osteoporosis. Approximately 80% of Canadians who have sustained a fracture due to osteoporosis do not receive appropriate care, leaving them at an elevated risk for subsequent fractures, deconditioning, and premature death.1 Many clinical practice guidelines exist on the management of osteoporosis and fracture prevention. Several of them have separate definitions for patients deemed very high and high risk for fracture and, as such, have specific criteria for the use of anabolic and antiresorptive treatments.